Epidemiologic Risk Factors for In Situ and Invasive Breast Cancers Among Postmenopausal Women in the National Institutes of Health-AARP Diet and Health Study. Issue 12 (16th June 2017) - Mullooly, Maeve; Khodr, Zeina G; Dallal, Cher M; Nyante, Sarah J; Sherman, Mark E; Falk, Roni; Liao, Linda M; Love, Jeffrey; Brinton, Louise A; Gierach, Gretchen L
Abstract: Comparing risk factor associations between invasive breast cancers and possible precursors may further our understanding of factors related to initiation versus progression. Accordingly, among 190, 325 postmenopausal participants in the National Institutes of Health-AARP Diet and Health Study (1995–2011), we compared the association between risk factors and incident ductal carcinoma in situ (DCIS; n = 1, 453) with that of risk factors and invasive ductal carcinomas ( n = 7, 525); in addition, we compared the association between risk factors and lobular carcinoma in situ (LCIS; n = 186) with that of risk factors and invasive lobular carcinomas ( n = 1, 191). Hazard ratios and 95% confidence intervals were estimated from multivariable Cox proportional hazards regression models. We used case-only multivariable logistic regression to test for heterogeneity in associations. Younger age at menopause was associated with a higher risk of DCIS but lower risks of LCIS and invasive ductal carcinomas ( P for heterogeneity < 0.01). Prior breast biopsy was more strongly associated with the risk of LCIS than the risk of DCIS ( P for heterogeneity = 0.04). Increased risks associated with use of menopausal hormone therapy were stronger for LCIS than DCIS ( P for heterogeneity = 0.03) and invasive lobular carcinomas ( P for heterogeneity < 0.01). Associations were similar for race, age at menarche, age at first birth, family history, alcohol consumption, and smoking status, which suggests that most risk factor associations are similar for in situ and invasive cancers and may influence early stages of tumorigenesis. The differential associations observed for various factors may provide important clues for understanding the etiology of certain breast cancers.